2000
DOI: 10.1016/s1387-6473(00)00084-1
|View full text |Cite
|
Sign up to set email alerts
|

Warm absorbers in narrow-line Seyfert 1 galaxies

Abstract: Warm absorbers are an important new tool for investigating the conditions within the central regions of active galaxies. They have been observed in ∼50% of the well-studied Seyfert galaxies and have also been detected in quite a number of Narrow-line Seyfert 1 galaxies (NLSy1). Here, we present a study of the X-ray properties of several NLSy1s with focus on their warm absorbers: (a) An analysis of all ROSAT PSPC observations of NGC 4051 including new ones is performed, which reveals variability by a factor ∼30… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 12 publications
5
38
0
Order By: Relevance
“…The ROSAT All-Sky Survey detected soft X-ray outbursts from a number of galaxies with no previous history of of nuclear activity. Roughly half a dozen of these events had the properties of a tidal disruption flare (Komossa 2002 and references therein), and follow-up optical spectroscopy of the candidate galaxies confirmed that at least two were subsequently inactive (Gezari et al 2003). The mean event rate inferred from these outbursts is roughly consistent with theoretical predictions (Donley et al 2002).…”
Section: Constraining the Consumption Ratesupporting
confidence: 63%
See 1 more Smart Citation
“…The ROSAT All-Sky Survey detected soft X-ray outbursts from a number of galaxies with no previous history of of nuclear activity. Roughly half a dozen of these events had the properties of a tidal disruption flare (Komossa 2002 and references therein), and follow-up optical spectroscopy of the candidate galaxies confirmed that at least two were subsequently inactive (Gezari et al 2003). The mean event rate inferred from these outbursts is roughly consistent with theoretical predictions (Donley et al 2002).…”
Section: Constraining the Consumption Ratesupporting
confidence: 63%
“…Alexander (2003Alexander ( , 2005 reviews the physics of star-star and star-SBH interactions, with an emphasis on dissipative processes and on the nucleus of the Milky Way; as noted above, such processes are of less importance in the nuclei of most galaxies known to contain SBHs. Komossa (2002Komossa ( , 2003 reviews the observational evidence for interaction of single and binary SBHs with stars and gas in galactic nuclei. (For a more theoretically oriented review of binary SBHs, see Merritt & Milosavljević 2005.…”
Section: Noted Thatmentioning
confidence: 99%
“…The observed events match basic predictions expected from stars tidally disrupted by supermassive black holes at the centers of the flaring galaxies (see Komossa & Bade 1999, Komossa 2002 for a much more detailed discussion).…”
Section: Joint X-ray Lightcurve Of the Flare Eventssupporting
confidence: 79%
“…This paper concentrates on observations of giant-amplitude X-ray flares from the centers of several (optically non-active) galaxies, and their interpretation in terms of stellar tidal disruption events. Several X-ray outbursts were detected with ROSAT (review by Komossa 2002); three optically non-active galaxies and the HII galaxy NGC 5905 (Komossa & Bade 1999) which shows a lowluminosity high-excitation core detected with HST (Gezari et al 2003), either excited by the flare emission, or, perhaps more likely, a permanent very low-luminosity AGN. Here, I summarize recent Chandra follow-up observations which allowed some key tests of the previous suggestion (Komossa & Bade 1999) that we have observed flares from stars tidally disrupted by supermassive black holes (see Komossa et al 2004 for the full results).…”
Section: Introductionmentioning
confidence: 99%
“…Komossa 2000, and references therein). This highly ionized material, called "warm absorber", has also been detected in about 50% of type 1 Active Galactic Nuclei (AGNs), both Seyfert 1s (Halpern 1982;Reynolds 1997;George et al 1998) and quasars (Piconcelli et al 2005).…”
Section: Introductionmentioning
confidence: 99%